Acupressure And Zingiber Officinale Therapy On The Intensity Of Menstrual Pain In Adolescent Girls - Neny Yuli Susanti (PROFESSIONAL HEALTH JOURNAL, 2024)
The onset of menstruation is one of the first real changes that teenagers experience. Even though menstruation is a normal, natural process, some women experience discomfort during menstruation, including dysmenorrhea (low back pain), irregular menstruation, or lower abdominal pain. To relieve dysmenorrhea, one of the options is to use methods other than drugs. To relieve the severity of menstrual pain or dysmenorrhea, this research will examine the efficacy of acupressure and ginger drinks, as well as variations in administration and the effects of ginger drinks. This research used a quasi-experimental design with a pretest-posttest strategy with two groups. Thirty women aged eighteen to twenty-one years participated in the study (15 in the acupressure group and 15 in the red ginger group). To select the sample, the researcher used a purposive sampling technique. The research results revealed that acupressure, ginger drink, and a combination of the two were effective in alleviating the symptoms of menstrual pain and dysmenorrhea in adolescent girls. However, the effects of ginger drinks and acupressure treatments are not additive. In the Adolescent Girls Age Group